SYARIAH DAN HAK ASASI MANUSIA TELAAH ATAS PEMIKIRAN ABDULLAH AHMED AN-NA'IM - Hartono, Hartono (At-Tawazun, Jurnal Ekonomi Syariah, 2020)
This theme often faces to face, sharia with its theocentric dominance and human rights with its anthropocentricity. Sharia is understood in the context of back to the quran and hadith as appropriate, however, this understanding must require tools that support it so that what is contained in it can be adjusted in the current context. Meanwhile, the conceptions of human rights in the Quran and hadith are also widely conveyed, because it is important to understand them so that they are compatible in space and time at the same time.